A Radial Glia Fascicle Leads Principal Neurons from the Pallial-Subpallial Boundary into the Developing Human Insula - González-Arnay, Emilio; González-Gómez, Miriam; Meyer, Gundela (Frontiers in Neuroanatomy, 2017)
The human insular lobe, in the depth of the Sylvian fissure, displays three main cytoarchitectonic divisions defined by the differentiation of granular layers II and IV. These comprise a rostro-ventral agranular area, an intermediate dysgranular area, and a dorso-caudal granular area. Immunohistochemistry in human embryos and fetuses using antibodies against PCNA, Vimentin, Nestin, Tbr1, and Tb2 reveals that the insular cortex is unique in that it develops far away from the ventricular zone (VZ), with most of its principal neurons deriving from the subventricular zone (SVZ) of the pallial-subpallial boundary (PSB). In human embryos (Carnegie stage 16/17), the rostro-ventral insula is the first cortical region to develop; its Tbr1+ neurons migrate from the PSB along the lateral cortical stream. From 10 gestational weeks (GW) onward, lateral ventricle, ganglionic eminences, and PSB grow forming a C-shaped curvature. The SVZ of the PSB gives rise to a distinct radial glia fiber fascicle (RGF), which courses lateral to the putamen in the external capsule. In the RGF, four components can be established: PF, descending from the prefrontal PSB to the anterior insula; FP, descending from the fronto-parietal PSB toward the intermediate insula; PT, coursing from the PSB near the parieto-temporal junction to the posterior insula, and T, ascending from the temporal PSB and merging with components FP and PT. The RGF fans out at different dorso-ventral and rostro-caudal levels of the insula, with descending fibers predominating over ascending ones. The RGF guides migrating principal neurons toward the future agranular, dysgranular, and granular insular areas, which show an adult-like definition at 32 GW. Despite the narrow subplate, and the absence of an intermediate zone except in the caudal insula, most insular subdivisions develop into a 6-layered isocortex, possibly due to the well developed outer SVZ at the PSB, which is particularly prominent at the level of the dorso-caudal insula. The small size of the initial PSB sector may, however, determine the limited surface expansion of the insula, which is in contrast to the exuberant growth of the opercula deriving from the adjacent frontal-parietal and temporal VZ/SVZ.